Ethyl 2-(2-oxo-4-phenyl-2,3-dihydro-1H-1,5-benzodiazepin-1-yl)acetate - Ballo, D.; Ahabchane, N.H.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered ring in the title compound, C(19)H(18)N(2)O(3), adopts a boat conformation with the two phenylene C atoms representing the stern and the methylene C atom the prow. The dihedral angle between the best plane through the seven-membered ring (r.m.s deviation = 0.343 A) and the phenyl substituent is 31.9 (1)degrees. The dihedral angle between this best plane and the best plane through the ethoxycarbonylmethyl substituent (r.m.s. deviation = 0.058 A) is 72.2 (1)degrees